Retrofitting rurality: Embodiment and emplacement in disability narratives. (April 2017) - Cella, Matthew J.C.
Abstract: In this paper I examine the ways in which people with physical and sensory disabilities challenge normative (even ableist) constructions of the body-environment dyad. Drawing on insight from eco-phenomenologists and rural scholars, I analyze autobiographical narratives by people with disabilities to illustrate the complex entanglement between embodiment and emplacement. Collectively, these disability life narratives present a series of reconstructive strategies – what I call retrofit tactics – that address some of the commonplaces regarding normative rural embodiment and that make corrective adjustments to rurality (retrofits) to accommodate a wider range of embodied experiences. In the course of the article, I identify four such retrofit strategies, which include (1) expanding conceptions of rural embodiment beyond normative definitions, (2) underscoring the importance of attentiveness to one's body-in-nature, (3) emphasizing and embracing the interdependency of bodies (rather than an isolationist paradigm), and (4) highlighting the importance of language and narrative in the place-making process, particularly within rural environments that traditionally privilege mobility. I am especially interested in demonstrating how the category of disability both challenges and sharpens our understanding of what it means to inhabit rural places and to move between rural and urban spaces. Highlights: Autobiographies are a valuable tool through which to explore definitions of rurality. Fashioning an inclusive rurality requires integration of the disability perspective. Identifies tactics that retrofit rurality by incorporating disability experience.